Systems metabolic engineering - Lee, Sang Yup; Wittmann, Christoph (Springer Netherlands, 2012)
Systems Metabolic Engineering is changing the way microbial cell factories are designed and optimized for industrial production.   Integrating systems biology and biotechnology with new concepts from synthetic biology, it enables the global analysis and engineering of microorganisms - and bioprocesses at super efficiency and versatility otherwise not accessible. Without doubt, systems metabolic engineering is a major driver towards bio-based production of chemicals, materials and fuels from renewables and thus one of the core technologies of global green growth. In this book, Christoph Wittmann and Sang-Yup Lee have assembled the world leaders on systems metabolic engineering and cover the full story - from genomes and networks via discovery and design to industrial implementation practises. This book is a comprehensive resource for students and researchers from academia and industry interested in systems metabolic engineering. It provides us with the fundament to targeted engineering of microbial cells for sustainable bio-production and stimulates those who are interested to enter into this exiting field.